Sufism and theology - Shihadeh, Ayman (Edinburgh University Press, 2007)
Sufism and Theology are two major currents in Islamic thought and religious culture, and over the centuries they have displayed immense diversity and intellectual richness. This book takes a flexible and inclusive approach to these trends, revealing both how Sufis approached theological traditions and themes and practised theology themselves, and how theologians approached different aspects of Sufism.Comprising chapters by leading specialists in the field, this volume is the first to explore the historically complex interface between these two major currents, highlighting key points of tension and interaction. Taking us through an array of subjects, including hermeneutics, psychology and metaphysics, light is shed on major intellectual trends and figures from the 12th century up to the modern period. These range from al-Hallaj, Ibn ́⁰₈Arabi and Ibn Sab́⁰₈in, to Fakhr al-Din al-Razi, Ibn Taymiyya, Haydar Amuli and Ibn Kemal Pasha, from the Ottoman context to the Safavid, and from Sunnism to Shí⁰₈ism.In sum, this book offers readers a balanced perspective of the overall history of the relationship between Sufism and Theology.